Адміністративно-правове забезпечення цивільного захисту на регіональному рівні в Україні : автореферат дисертації - Остап'юк, А. Ю.; Ostapiuk, A. Yu. (Харківський національний університет внутрішніх справ, 2024)
У дисертації наведено теоретичне узагальнення та нове вирішення наукового завдання, яке полягає у тому, щоб визначити сутність та особливості адміністративно-правового забезпечення цивільного захисту на регіональному рівні в Україні, а також на основі узагальнення позитивного вітчизняного та зарубіжного досвіду розробити пропозиції та рекомендації, спрямовані на вдосконалення адміністративного законодавства, що регулює відповідні правовідносини. Визначаються методологічні засади забезпечення цивільного захисту на регіональному рівні в Україні, а також характеризується адміністративно-правовий механізм забезпечення цивільного захисту на регіональному рівні в Україні. Визначаються напрями удосконалення адміністративно-правового забезпечення цивільного захисту на регіональному рівні в Україні.

The author has proposed to understand civil protection as a system of measures of legal, organisational, economic, engineering, technical, sanitary and hygienic nature, etc. which are implemented by specially authorized entities with the aim of preventing, counteracting and preventing emergencies and dangerous events, and also overcoming their consequences. It has been substantiated that civil protection at the regional level is characterised by the following features: a) it is regulated by a number of legal acts of different legal force, among which a special place is given to by-laws and local regulations; b) the specifics of civil protection at the regional level directly depend on the national policy in this area; c) the choice of instruments and means of civil protection directly depends on the individual characteristics of each region; d) there is a special circle of entities authorised to carry out activities aimed at ensuring civil protection within a particular region. It has been noted that the importance of ensuring civil protection at the regional level is revealed in the tasks and principles of such activities. It has been argued that the tasks of the relevant provision are: 1) to protect the population of a certain region from dangerous and emergency situations or events, and also to prevent their occurrence in the future; 2) to create the necessary conditions for maintaining social, political, environmental, etc. stability in the region; 3) to correct and timely eliminate the consequences of emergencies and dangerous events which affect the social, environmental and technical infrastructure of the region, the normal course of life of the population, the moral and psychological state of the residents of the relevant territory, etc; 4) to support the effectiveness and stability of public authorities' activities in case of emergencies or events; 5) to form a regulatory, legal, organisational, managerial and economic basis for the functioning of entities whose activities are aimed at implementing civil protection measures within a certain region; 6) to establish domestic and international relations and partnerships for innovative development of the civil protection system in certain regions. The author has highlighted that ensuring civil protection at the regional level is a complex legal phenomenon not only from theoretical but also from a practical point of view. Its implementation is carried out in an orderly manner due to the division into the following levels: 1) regional; 2) district; 3) local; and 4) local-situational. At each of these levels, the task of ensuring civil protection is performed by a separate group of entities that have not only legislatively defined powers, but also a corresponding interest in a high level of security in the region that falls within their competence.
Administrative and legal provision of civil protection at the regional level in Ukraine
Keywords: Україна; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 081 – Право; 12.00.07; цивільний захист; адміністративно-правове регулювання; зарубіжний досвід; воєнний стан; взаємодія; координація; публічне управління; умови воєнного стану; публічне адміністрування; контроль; нагляд; адміністративне законодавство; Ukraine; civil protection; administrative and legal regulation; foreign experience; martial law conditions; interaction; coordination; public administration; administrative legislation